(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
[M(LH) X2] general complex formula where M= divalent metal of Zn, Cd and Hg ;LH = Schiff base 4-acetylpyridinen1benzoyl hydrazone1and X = chloride ion, were1synthesized1 . All complexes structures1 were analyzed by Infrared spectroscopy1, and characterized1by (C,H,N) analysis, uv-visible and conductivity measurements. The values of molar conductance in dimethyl sulfoxide indicate nonelectrolytes properties. The spectral studies indicate that all complexes are distorted tetrahedral geometry. The ligand (LH) coordinates through nitrogen׳s imine group (>C=N-) and oxygen’s carbonyl group.